Robust predictive dual-loop control method based on Lyapunov function stability and energy equilibrium though double-core processors for active power filter. (July 2017) - Yue, Yufei; Chen, Yandong; Luo, An; Ma, Fujun; Xu, Qianming; He, Zhixing
Graphical abstract: Highlights: Robust predictive dual-loop control based on LFS and energy equilibrium is proposed. RPCC-LFS enhances self-adaptive capability, dynamic response, and accuracy. Energy equilibrium PI controller remains dc-link voltage stable. Proper control parameters are achieved by system stability and dynamics analysis. Abstract: In this paper, a robust predictive dual-loop control method based on Lyapunov function stability and energy equilibrium for active power filter (APF) is proposed to improve the anti-interference performance and self-adaptive capability of system. The proposed control method mainly includes robust predictive current control based on Lyapunov function stability (RPCC-LFS) in the inner current loop and energy equilibrium proportional-integrator (PI) control in the outer dc-link voltage loop. The RPCC-LFS is proposed to enhance self-adaptive capability when the output filter inductors vary, speed up the dynamic response, and improve the tracking accuracy when the loads fluctuate. The energy equilibrium PI controller is proposed to maintain the dc-link voltage stable and suppress the transient impulse. The stability and dynamic response of the proposed control system are analyzed in detail, and the proper control parameters are selected. A specific hardware and software design program based on double-core processors DSP + FPGA is thoroughly given out. Finally, the comparative simulations and experiments verified the validity of the proposed method.